GAMBARAN PENGETAHUAN DAN SIKAP WANITA USIA SUBUR YANG BELUM MENIKAH TENTANG TRADISI BADAPU DI WILAYAH KERJA PUSKESMAS SINGKIL KABUPATEN ACEH SINGKIL TAHUN 2013 - eliana tarigan; Ernawati Nasution; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Aceh Singkil community has a tradition of eating certain foods taboo to implement the postpartum mother at Badapu tradition. Badapu tradition is a tradition passed down for generationsthat should be done by the post partum mother from body heat to do on the abstinence of somefoods. Because women of reproductive age who are unmarried will undergo a period of postpartum later, so it is necessary to know of how their knowledge and attitudes about Badaputradition.The study was a descriptive cross-sectional design. This study aims to describe theknowledge and attitudes of women of reproductive age who are not married on Badapu tradition inthe Community Health Centers Singkil. Population is women of reproductive age who areunmarried. Sampling was done by purposive sampling in 16 villages. Sample of 100 people selectedby proportional allocation. Collecting data on the characteristics, knowledge and attitudes throughinterviews using questionnaires. Data were analyzed descriptively and presented in a frequencydistribution table.The results showed that the majority of women of reproductive age who are not marriedhave a good knowledge of the tradition Badapu (93%) and have a good attitude about traditionBadapu (49%), while the correlation between knowledge and attitude of women of reproductive agehave no significant relationship (p> 0.904)There should be a counseling approach and performed by Nutrition Workers of CommunityHealth Centers and Midwive to provide the KIE of Nutrition and correct direction in implementingBadapu tradition.Keywords: Knowledge, Attitudes, Women of Reproductive Age, Badapu Tradition.